Almensvellets affortryllelse - Neoliberale anfægtelser af det fælles bedste - Jensen, Jacob (Slagmark - Tidsskrift for idéhistorie, 2020)
This article revisits the origins of neoliberalism, arguing that it arose in the socialist calculation debates in the 1920s and 1930s. In these debates, Ludwig von Mises and Friedrich von Hayek contested socialist conceptions of the public interest, claiming that the market’s price mechanism was far better able to represent the many diffe- rent preferences that a modern mass society consists of. The market, they stressed, was far more efficient at coordinating the economy than state planners who would never be able to calculate or aggregate the necessary data on people’s preferences, which was required to direct markets. This contestation of the common good, the article argues, has been a mainstay throughout neoliberalism’s intellectual history, serving as the revolving point of post-war analyses of government failure.